2009
DOI: 10.1016/j.otohns.2009.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity of a simulator for myringotomy with ventilation tube insertion

Abstract: Our model is a valid platform for simulating myringotomy with ventilation tube insertion. The model discriminates novices from non-novices, has a learning curve, and is perceived to be a valuable and realistic teaching tool by users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 15 publications
1
42
0
1
Order By: Relevance
“…Pour toutes ces raisons, plusieurs systèmes d'entraînement ont été développés : faisant appel à des cadavres, des simulateurs en acrylique, des modèles faits-maison comme le nôtre (ex., le Wigan ou le Bradford Grommet Trainer), ainsi que des modèles virtuels dernier cri [5][6][7][8][9]. Les cadavres et les simulateurs virtuels, cependant, représentent un coût important pour les services hospitaliers, d'où la recherche d'alternatives comme le simulateur que nous décrivons ici.…”
Section: Discussionunclassified
“…Pour toutes ces raisons, plusieurs systèmes d'entraînement ont été développés : faisant appel à des cadavres, des simulateurs en acrylique, des modèles faits-maison comme le nôtre (ex., le Wigan ou le Bradford Grommet Trainer), ainsi que des modèles virtuels dernier cri [5][6][7][8][9]. Les cadavres et les simulateurs virtuels, cependant, représentent un coût important pour les services hospitaliers, d'où la recherche d'alternatives comme le simulateur que nous décrivons ici.…”
Section: Discussionunclassified
“…[8][9][10][11][12][13][14][15][16][17][18][19] Two models showed face validity data, 16,18 three studies reported on the effect of iteration, 14,15,19 and one included construct validity data. 15 The remainder were purely descriptive articles. No simulators incorporated human or animal tissue but two utilised virtual reality.…”
Section: Literature Searchmentioning
confidence: 99%
“…Numerous models have been described ranging from DIY models based on readily available materials 12 to more complex physical models 13,14 . In addition, a VR simulation model for myringotomy and tube insertion with supporting haptic feedback has been developed 15–18 .…”
Section: Introductionmentioning
confidence: 99%